Pharmacokinetics and immunogenicity of eftozanermin alfa in subjects with previously-treated solid tumors or hematologic malignancies: results from a phase 1 first-in-human study - Biesdorf, Carla; Guan, Xiaowen; Siddani, Satya R.; Hoffman, David; Boehm, Nils; Medeiros, Bruno C.; Doi, Toshihiko; de Jonge, Maja; Rasco, Drew; Menon, Rajeev M.; Polepally, Akshanth R. (Cancer chemotherapy and pharmacology, 2024)
Purpose Eftozanermin alfa is a second-generation tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) receptor agonist that enhances death receptor 4/5 clustering on tumor cells to induce apoptosis. We report the pharmacokinetics and immunogenicity of eftozanermin alfa administered intravenously to 153 adults with previously-treated solid tumors or hematologic malignancies from the first-in-human, open-label, dose-escalation and dose-optimization study. Methods Dose escalation evaluated eftozanermin alfa monotherapy 2.5–15 mg/kg on Day 1 or Days 1/8 of a 21-day cycle. Dose optimization evaluated eftozanermin alfa monotherapy or combination therapy with either oral venetoclax 400–800 mg daily (eftozanermin alfa 1.25–7.5 mg/kg Days 1/8/15 of a 21-day cycle) or chemotherapy (eftozanermin alfa 3.75 or 7.5 mg/kg Days 1/8/15/22 of a 28-day cycle and FOLFIRI regimen [leucovorin, 5-fluorouracil, and irinotecan] with/without bevacizumab on Days 1/15 of a 28-day cycle). Results Systemic exposures (maximum observed concentration [C max ] and area under the concentration–time curve [AUC]) of eftozanermin alfa were approximately dose-proportional across the entire dose escalation range with minimal to no accumulation in Cycle 3 versus Cycle 1 exposures. Comparable exposures and harmonic mean half-lives (35.1 h [solid tumors], 31.3 h [hematologic malignancies]) were observed between malignancy types. Exposures (dose-normalized C max and AUC) in Japanese subjects were similar to non-Japanese subjects. Furthermore, eftozanermin alfa/venetoclax combination therapy did not have an impact on the exposures of either agent. Treatment-emergent anti-drug antibodies were observed in 9.4% (13/138) of subjects. Conclusions The study results, including a pharmacokinetic profile consistent with weekly dosing and low incidence of immunogenicity, support further investigation of eftozanermin alfa. Trial registration ID: NCT03082209.